Prevalence of hypertension and associated anthropometric indices among the non-medical employees working in medical college Thiruvananthapuram: a cross-sectional study - Nair, Akhila M.; Jayakumar, Akhila; Sreedharan, Mini S.; Raj, Akhil; Abhinav, A. K.; Shahina, Ajmal A.; Sahu, Amala P. (International Journal Of Community Medicine And Public Health, 2024)
Background: Hypertension is a major public health problem. Globally 1.28 billion adults aged 30-79 years have hypertension and among this 46% were undiagnosed. Kerala is one state undergoing epidemiological transition and having high prevalence of hypertension. So, we did this study to estimate the proportion of hypertension among non-medical employees of Medical College Thiruvananthapuram. Methods: A cross-sectional study was conducted among 202 non-medical employees of medical college Thiruvananthapuram. Data was collected using an investigator administered questionnaire. Anthropometric indices were measured and recorded. Blood pressure (BP) was recorded twice in a gap of 15 min for each participant in sitting position using mercury sphygmomanometer. Mean systolic BP (SBP) and diastolic BP (DBP) was calculated to confirm hypertension. Participants those who were already detected as hypertensive and on treatment were also noted. Data was analysed using SPSS software version 27. Results: Prevalence of hypertension in the study population was 61/202 (30.19%). Among the hypertensive 39 (63.9%) were already detected and on treatment and 22 (36.1%) were undiagnosed. Among already detected hypertensive 13 (33.3%) were found to be inadequately treated. Hypertension was found to be associated with waist circumference and BMI. Conclusions: The study population was found to have high prevalence of hypertension and having association with waist circumference and BMI. The rule of halves for depicting the trend of hypertension in study population can be used as a tool to deduce various interventions in the community.